Exposure to threatening and violent behaviour among single mothers. The significance of lifestyle neighbourhood and welfare situation - Estrada, Felipe (The British journal of criminology, 2004)
The objective of this article is to study violent victimization among single mothers. This is mainly achieved by examining variations within the group of single mothers. The study is based on the Annual Survey of Living Conditions conducted by Statistics Sweden. The analysis includes a total of 1,713 single mothers. One of the central issues in this study is to examine the significance of factors related to participation in public entertainment, residential neighbourhood and resource deficiencies at the individual level. One important conclusion from the study is that differences in levels of exposure to violence, both within the group of single mothers and between this group and other women, are primarily related to levels of individual welfare resources